UV-curable antibacterial ionic polysilsesquioxanes: Structure-property relationships investigating the effect of various cations and anions - Lee, Albert S.; Lee, Jin Hong; Choi, Seung-Sock; Cho, Kie Yong; Yu, Seunggun; Koo, Chong Min; Baek, Kyung-Youl; Hwang, Seung Sang (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
A series of inorganic-organic hybrid UV-curable ionic polysilsesquioxanes were synthesized through Menshutkin reactions with various tertiary amine vinyl or methacrylic monomers to quantitatively quaternize various alkyl-halide ladder-like functionalized polysilsesquioxanes. The effect of quaternary ammonium salt cation, anion, as well as UV-curing were examined. Obtained ionic polysilsesquioxanes exhibited exceptional thermal stability ( > 350 degrees C), high surface hardness (6H), high refractive index ( > 1.66), and substantial decrease in brittleness index. In addition to the excellent hardcoating properties, the ionic groups imbued antibacterial properties against gram positive and gram negative bacteria, which may allow for applications in flexible electronic devices.
Keywords: HYBRID; POLYMERS; COATINGS; MEMBRANES; OLIGOSILSESQUIOXANES; COMPOSITES; EFFICIENCY; BACTERIA; DESIGN; SILANE